Environmental risk mitigation by biodiesel blending from eichhornia crassipes: Performance and emission assessment - Abdul Wahhab, H.A. (MDPI, 2021)
The aggressive growth of Eichhornia crassipes (Water Hyacinth) plants causes severe damage to the irrigation, environment, and waterway systems in Iraq. This study aims to produce, characterize, and test biofuel extracted from the Eichhornia crassipes plant in Iraq. The extracted biodiesel was mixed at 10, 20, and 40 with neat diesel to produce three biodiesel samples. The methodology consists of the physiochemical properties of the samples that were characterized. The performance of the IC engine fueled by neat and biodiesel samples was measured under various operational conditions. The exhaust gases were analyzed to estimate the compounds to assess the environmental impact. The results showed that the density and viscosity of mixtures increase and the calorific value decrease with biodiesel. The engine test showed that the diesel + 10BE, diesel + 20BE, and diesel + 40BE enhanced brake thermal efficiency using 2.6, 4.2, and 6.3, respectively, compared to neat diesel. Exhaust tests show a slight reduction, of 0.85â3.69 and 2.48â6.93, in CO and HC emission, respectively. NOx is higher by 1.87â7.83 compared with neat diesel. The results revealed that biodiesel blended from Eichhornia crassipes is a viable solution to mitigate the drastic impact on the environment and economy in Iraq. The blended biodiesel has good potential to be mixed with the locally produced diesel from oil refineries. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.